Review of Coca Wine. Angelo Mariani’s Miracolous Elixir and the Birth of Modern Advertising - Ehrinpeis, Andrew B. (European Review of Latin American and Caribbean Studies, 2019)
Coca Wine. Angelo Mariani’s Miracolous Elixir and the Birth of Modern Advertising, by Aymon de Lestrange. Park Street Press, 2018